Philip I of Portugal - A foreingner? About the naturality of royal dinasties in early modern times (Estudios de Historia de España, 2019)
This study discusses the question if Philipp II can be considered a foreigner in Portugal when he becomes King in that kingdom. First of all, the different concepts of naturality and foreigner for vassals and kings will be presented. In case of the kings there are two established concepts of being natural: one as a synonym of legitimate and another one which requires ascendency, the domination of the language and the usages of the kingdom as requirements. While the first one is purely dynastic, the other one depends more on the royal individual in each case. After stating the importance and the appropriateness of naturality by showing several cases of early modern Europe, the study focusses on the particular case of Philipp in Portugal. We reach to the conclusion that Philipp cannot be considered a foreigner in Portugal, given that he matches the established criteria of his time.
Keywords: Early Modern history; Portuguese history; Natural king; Philipp II; Dynasties